Implementasi Kompetensi Guru Pendidikan Agama Kristen dalam Pembelajaran secara Daring - Riany Prisila Pondaag; Johanna P Setlight; Meyke M. Mamahit (Jurnal Ilmiah Wahana Pendidikan, 2022)
The purpose of this study was to describe and analyze the implementation of the competence of Christian Religious Education teachers in the online learning process at the Rehobot Christian Elementary School, Manado. The research method used in this research is a descriptive qualitative research method. The results of the study indicate that the implementation of the competence of Christian Religious Education Teachers in online learning at Rehobot Christian Elementary School has not been maximally implemented. The number of inhibiting factors needs to be communicated jointly between the Principal, Christian Religious Education Teachers and Parents so that the best solution is found for the development of student learning during online learning.